Time variability of Neptune’s horizontal and vertical cloud structure revealed by VLT/SINFONI and Gemini/NIFS from 2009 to 2013 - Irwin, PGJ; Fletcher, LN; Tice, D; Owen, SJ; Orton, GS; Teanby, NA; Davis, GR (Elsevier, 2016)
New observations of Neptune’s clouds in the near infrared were acquired in October 2013 with SINFONI on ESO’s Very Large Telescope (VLT) in Chile. SINFONI is an Integral Field Unit spectrometer returning a 64 × 64 pixel image with 2048 wavelengths. Image cubes in the J-band (1.09 – 1.41 μm) and H-band (1.43 – 1.87 μm) were obtained at spatial resolutions of 0.1″and 0.025″per pixel, while SINFONI’s adaptive optics provided an effective resolution of approximately 0.1″. Image cubes were obtained at the start and end of three successive nights to monitor the temporal development of discrete clouds both at short timescales (i.e. during a single night) as well as over the longer period of the three-day observing run. These observations were compared with similar H-band observations obtained in September 2009 with the NIFS Integral Field Unit spectrometer on the Gemini-North telescope in Hawaii, previously reported by Irwin et al., Icarus 216, 141-158, 2011, and previously unreported Gemini/NIFS observations at lower spatial resolution made in 2011.